2019
DOI: 10.1002/cpt.1482
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics‐Driven Prediction of Antidepressant Treatment Outcomes: A Machine‐Learning Approach With Multi‐trial Replication

Abstract: We set out to determine whether machine learning–based algorithms that included functionally validated pharmacogenomic biomarkers joined with clinical measures could predict selective serotonin reuptake inhibitor (SSRI) remission/response in patients with major depressive disorder (MDD). We studied 1,030 white outpatients with MDD treated with citalopram/escitalopram in the Mayo Clinic Pharmacogenomics Research Network Antidepressant Medication Pharmacogenomic Study (PGRN‐AMPS; n = 398), Sequenced Treatment Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 62 publications
0
76
0
1
Order By: Relevance
“…Athreya et al [30] employed a random forest method, a conventional artificial intelligence and machine learning approach, to predict antidepressant therapy response (with AUC > 0.7 and accuracy > 69%). The multi-omics data in their study included the SNPs datasets.…”
Section: Study Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Athreya et al [30] employed a random forest method, a conventional artificial intelligence and machine learning approach, to predict antidepressant therapy response (with AUC > 0.7 and accuracy > 69%). The multi-omics data in their study included the SNPs datasets.…”
Section: Study Model Resultsmentioning
confidence: 99%
“…To predict antidepressant treatment response, various research studies [22][23][24][25][26][27][28][29][30] used conventional artificial intelligence and machine learning methods. For example, Kautzky et al [22] suggested that the random forest structure, a conventional artificial intelligence and machine learning method, correctly predicted 25% of responders for antidepressant treatment outcome based on genetic and clinical data.…”
Section: Applications In Treatment Predictionmentioning
confidence: 99%
“…Classification is a supervised learning approach in which the algorithm learns from a training set of correctly classified observations and uses this learning to classify new observations, where the output variable is discrete. Examples in biomedicine include classifying whether a tumor is benign or malignant [34], classifying the effects of individual single nucleotide polymorphisms on depression [7], the effects of ion channel blockage on arrhythmogenic risk in drug development [108], and the effects of chemotherapeutic agents in personalized cancer medicine [27].…”
Section: Potential Challenges and Limitationsmentioning
confidence: 99%
“…In biomedicine, the original area of big-data research was the identification of the human genome, which employed machine learning to construct consistent frames out of genome fragments. Since then, extensions of genomic studies involve large numbers of patients and controls in genome-wide association studies, which compare single nucleotide polymorphisms in patients versus controls [7,56]. Single nucleotide polymorphisms adjacent to coding sequences suggest which gene product might be involved in the disease.…”
Section: Applications and Opportunitiesmentioning
confidence: 99%
“…The challenge is to collect data reflecting the uniqueness of an individual's genome, metabolome, microbiome, current state of health (including pre‐existing medical conditions and concurrent medications), lifestyle (diet, stress level, physical activity, and sleep) on many people—a population—and allow machine‐learning algorithms to select the features most relevant and informative for a particular situation. Examples of artificial intelligence successfully applied to predict drug response are encouraging, but successful clinical implementation on a population basis will require further evidence from prospective clinical trials that the method performs as intended in a broader range of patients than originally studied.…”
Section: Population Data As a Solutionmentioning
confidence: 99%